2009
DOI: 10.1021/nl903362y
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Growth Kinetics, and Ledge Flow during Vapor−Solid−Solid Growth of Copper-Catalyzed Silicon Nanowires

Abstract: We use real-time observations of the growth of copper-catalyzed silicon nanowires to determine the nanowire growth mechanism directly and to quantify the growth kinetics of individual wires. Nanowires were grown in a transmission electron microscope using chemical vapor deposition on a copper-coated Si substrate. We show that the initial reaction is the formation of a silicide, eta'-Cu(3)Si, and that this solid silicide remains on the wire tips during growth so that growth is by the vapor-solid-solid mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
160
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 37 publications
9
160
1
1
Order By: Relevance
“…This shows that after the initial Cu source on the substrate has been consumed in the formation of Cu silicide nanocrystals, additional Si vapour supply results in the formation of pure, elemental Si NWs with well faceted Cu silicide tips (indicating a VSS NW growth mechanism). 26,44 When considering the growth mechanism for the Cu 15 Si 4 NWs in this report (depicted schematically Supporting Information Figure S10), there are noticeable parallels with the mechanisms proposed for the growth of the Ni silicide NWs. 31,32 There, the formation of Ni silicide crystallites was assumed to be a prerequisite for NW growth.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…This shows that after the initial Cu source on the substrate has been consumed in the formation of Cu silicide nanocrystals, additional Si vapour supply results in the formation of pure, elemental Si NWs with well faceted Cu silicide tips (indicating a VSS NW growth mechanism). 26,44 When considering the growth mechanism for the Cu 15 Si 4 NWs in this report (depicted schematically Supporting Information Figure S10), there are noticeable parallels with the mechanisms proposed for the growth of the Ni silicide NWs. 31,32 There, the formation of Ni silicide crystallites was assumed to be a prerequisite for NW growth.…”
Section: Resultsmentioning
confidence: 53%
“…Similarly, previous reports using Cu as a seed for elemental Si NW formation have always led the formation of orthorhombic Cu 3 Si catalyst seeds from the initial Cu nanoparticles. [36][37][38] It thus seems likely that pure Si NWs would have been formed in this system had Cu 3 Si crystallites been formed on the Cu substrate rather than Cu 15 Si 4 crystallites. Therefore, the phase of silicide (or germanide) formed on the substrate plays an important role in determining whether pure Si (or Ge) NWs or silicide (germanide) NWs form.…”
Section: Resultsmentioning
confidence: 99%
“…22 At present, most SiNWs used in nanodevices are synthesized by vaporliquid-solid (VLS) and vapor-solid-solid (VSS) growth processes. 33,125,127 Usually, SiNWs fabricated using VLS or VSS techniques have well-defined surfaces and well-controlled diameters. These SiNWsrelated FETs are quite sensitive because SiNWs have a high carrier mobility and high surface-to-volume ratio which ensures that mass carriers can be controlled easily by applying a weak electrical field on the gate.…”
Section: Conducting Polymer Nanomaterialsmentioning
confidence: 99%
“…Researchers have recently demonstrated that nanowires and/or whiskers may grow below the eutectic temperature without the presence of liquid phases in a vaporsolid-solid (VSS) mechanism which is explained by the size-dependent eutectic temperature depression hypothesis [19,20] or by the formation of catalyzing intermetallic phases. [21][22][23][24][25] However, prevailing studies on both VLS and VSS are mostly addressing nanowire and/or whiskers growth at the sub-micron and nanometric scale. We are not aware of reports on VLS or VSS features with supra-micron scales, as described in the present study.…”
Section: Introductionmentioning
confidence: 99%